Feminism, Science, and the Philosophy of Science
XX, 316 p.
Keywords: Feminism, Science, and the Philosophy of Science brings together original essays by both feminist and mainstream philosophers of science that examine issues at the intersections of feminism, science, and the philosophy of science. Contributors explore parallels and tensions between feminist approaches to science and other approaches in the philosophy of science and more general science studies. In so doing, they explore notions at the heart of the philosophy of science, including the nature of objectivity, truth, evidence, cognitive agency, scientific method, and the relationship between science and values.